2022
DOI: 10.1021/acs.inorgchem.2c01810
|View full text |Cite
|
Sign up to set email alerts
|

Output Enhancement of Triboelectric Nanogenerators Based on Hierarchically Regular Cadmium Coordination Polymers for Photocycloaddition

Abstract: Exploiting the well-arranged and tunable frameworks of crystalline materials, we herein report coordination polymers (CPs) with modulated hierarchical structures as triboelectric materials to construct and extend the application scope of triboelectric nanogenerators (TENGs). Different lengths and shapes of bridging ligands [4,4′-bpa = 1,2-bis­(4-pyridyl)­ethane, 4,4′-bpe = 1,2-bis­(4-pyridyl)­ethene, and 4,4′-bpp = 1,3-di­(2-pyridyl)­propane for 1, 2, and 3, respectively] were used to construct Cd-CP-based hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Moreover, the metal nodes in the framework establish a path for electron-jump transmission, thereby improving the frictional power-generation performance. 18,19 Therefore, the preparation of new MOF materials for frictional power-generation materials will expand the application range of TENGs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the metal nodes in the framework establish a path for electron-jump transmission, thereby improving the frictional power-generation performance. 18,19 Therefore, the preparation of new MOF materials for frictional power-generation materials will expand the application range of TENGs.…”
Section: Introductionmentioning
confidence: 99%
“…20 Starch comes in the field of TENG with some interesting tribo-property following their organic polymeric chains. 16,21 Several reports have been published in recent times based on starch and its composite which shows tremendous potential of starch is present in the field of TENG as a tribo active material. 22−30 Sarkar et al showed corn starch as a tribo positive bioplastic material, and later on, Khandelwal et al worked to enhance the electrical output by controlling the hydrophilic property of corn starch.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many strategies, people are currently interested in enhancing the electrical output and sensitivity of TENG by the incorporation of other materials into the well-known polymeric tribo materials. In recent years, some interesting reports based on composites have been published using the doping materials such as perovskite material (BaTiO 3 ) in polydimethylsiloxane (PDMS), K 0.5 Na 0.5 NbO 3 and polyvinylidene fluoride (PVDF), 2D nanomaterial (V 2 CT x ) in silicone solutions, covalent organic framework in poly­(vinyl alcohol) (PVA), metal organic framework in PDMS, different coordinated polymers in PVDF, and biomaterial lignin in PVA. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triboelectric nanogenerators (TENGs), being low-cost, structurally simple, easily fabricated, and highly energy-efficient, had been considered as an availably booming energy harvesting technology to directly harvest and convert mechanical energy (e.g., wave, vibration, raindrop, and wind) into electricity. Taking advantage of the intrinsic properties of TENGs, various strategies, including materials design, morphology control, charge injection, and device/structure optimization, had been used to assemble and integrate self-powered systems to improve the output performance by minimizing environmental influences. To meet the application requirements, the selection of suitable triboelectric materials, which were easy to modify and functionalize with excellent chemical stability and high selectivity, was the most effective approach to optimize and regulate the performance but still a challenge. Coordination polymers (CPs) or metal–organic frameworks (MOFs), composed of organic ligands and metal ions or clusters depending on the reticular chemistry, were a fascinating branch of crystalline materials with modular molecular structures. Benefiting from their reticular nature and well-defined platforms, the structure of CPs could be tuned by direct synthesis or postsynthetic modification to adjust their physicochemical properties. Owing to their tailorable structure and unique electronic capabilities, we explored how to perfectly incorporate CPs into organic polymers to adjust and control the TENGs’ outputs and broaden the application domain of CP-based TENGs for self-powered photoinduced systems, especially through visible light induced selective organic conversion, which was still in its infancy.…”
mentioning
confidence: 99%